Evolutionary nature of virtual experience - Lee, Kwan Min (2014)
Despite increasing dominance of virtual experience in our everyday life, there have been relatively few discussions on human responses to virtual experience. In the current paper, we define what virtual experience is based on the types of objects being experienced and the ways of experiencing. Then, we review three lines of research traditions examining the evolutionary nature of human responses to virtual experience—a) studies on Media Equation (ME) which investigate human responses to physical and/or social features of virtual objects; b) studies on Doubly Disembodied Language (DDL) which examine human responses to synthesized speech; and c) studies on human preferences for specific content types in media. Based on the general review of the three research traditions, we propose that people’s natural and social responses to virtual objects and contents come from the cognitive hijacking of the general thinking mechanism by specialized mind modules.